Monetary policy communication: Perspectives from former policy makers at the ECB - Michael Ehrmann; Sarah Holton; Danielle Kedan; Gillian Phelan (European Central Bank (ECB), 2021)
This paper reports the results of a survey of former members of the Governing Council of the European Central Bank, which sought their views on monetary policy communication practices, the related challenges and the road ahead. Pronounced differences across the respondent groups are rare, suggesting that there is broad consensus on the various issues. Respondents view enhancing credibility and trust as the most important objective of central bank communication. They judge communication with financial markets and experts as extremely important and adequate, but see substantial room for improvement in the communication with the general public. The central bank objective is widely seen as the most important topic for monetary policy communication, and several respondents perceived a need for clarification of the ECB's inflation aim, citing the ambiguity of the "below, but close to, 2%" formulation that was in place at the time of the survey.
Keywords: E52; E58; 330; monetary policy; central bank communication; survey